Adolescent Peer Groups And Drug Abuse - Radovanovic, Ivana D; Spasić, Danijela V.; Radovanović, Dobrivoje M. (Sociološki pregled, 2020)
Drug abuse is an important problem of the modern age. Impact that drug abuse has on society, the state and the health of individuals requires fundamental and urgent scientific research on all its aspects. Research into the etiology of drug abuse in the youth population in Serbia is one of such projects. This research was carried out on a representative sample of 1,287 secondary school students in Belgrade, divided into two groups: drug abusers and those who do not have contact with drugs. The aim of this paper was to identify risk factors within peer groups that could have a predictive value and serve as a basis for preventive interventions. Data analysis was done with canonical discriminant analysis, separately for boys and girls. The results of the study have shown that among adolescents there are three forms of drug abuse: 1) use only, 2) use and distribution, and 3) drug distribution only. The predicates of these behaviors belonging to peer groups are: the pressure by group on members to use drugs, the perception of an individual that members of the group use drugs, the use of alcohol in the group, the involvement of certain members of the group in crime, and the positive attitude of members of the group towards law violations. Predictive effects of these variables vary depending on the type of drug abuse and of the gender of respondents.
Keywords: drug abuse; adolescents; peer influence